Communication skills predict social-emotional competencies - Rautakoski Pirkko; af Ursin Piia; Carter Alice S.; Kaljonen Anne; Nylund Annette; Pihlaja Päivi (Elsevier, 2022)
Introduction: Studies have shown that many children with early language difficulties also have delays in social-emotional competencies as well as social-emotional and behavioral problems. It is unclear if these conditions are causally related, if they share a common underlying etiology, or if there are bidirectional effects. Studies investigating these associations have mostly involved children who are already using words to communicate, but it is important to know whether delays in preverbal communication and language development have any effects on these associations. The aim of the present study was to examine associations between preverbal communication and early verbal skills in infancy and subsequent social-emotional competencies and ensuing social-emotional and behavioral problems in early toddlerhood. The role of background factors known to influence early language development was also examined.
Methods: The sample consisted of 395 children (51.6% boys) from the Finnish Steps Study cohort. Language was assessed at age 13 months (+ 1 month) with the MacArthur Communicative Development Inventory for Infants (CDI-I), and the social-emotional domain was assessed at age < 17 months with the Brief Infant–Toddler Social and Emotional Assessment (BITSEA).
Results: Infants with lower preverbal gestural communication and receptive language skills had a higher risk of delays in social-emotional competencies in toddlerhood than children with better communication skills, but not of elevated social-emotional and behavioral problems.
Conclusions: The results indicate that lower early communication skills can predict delays in the development of social-emotional competencies, which has been found to be a risk factor for later development of social-emotional and behavioral problems. It is important to monitor early communication skills to provide guidance to parents in supporting early pragmatic communication and language development in infancy, if needed.